“Embodied Body Language”: an electrical neuroimaging study with emotional faces and bodies - Marta Calbi (Nature Portfolio, 2017)
Abstract To date, most investigations in the field of affective neuroscience mainly focused on the processing of facial expressions, overlooking the exploration of emotional body language (EBL), its capability to express our emotions notwithstanding. Few electrophysiological studies investigated the time course and the neural correlates of EBL and the integration of face and body emotion-related information. The aim of the present study was to investigate both the time course and the neural correlates underlying the integration of affective information conveyed by faces and bodies. We analysed EEG activities evoked during an expression matching task, requiring the judgment of emotional congruence between sequentially presented pairs of stimuli belonging to the same category (face-face or body-body), and between stimuli belonging to different categories (face-body or body-face). We focused on N400 time window and results showed that incongruent stimuli elicited a modulation of the N400 in all comparisons except for body-face condition. This modulation was mainly detected in the Middle Temporal Gyrus and within regions related to the mirror mechanism. More specifically, while the perception of incongruent facial expressions activates somatosensory-related representations, incongruent emotional body postures also require the activation of motor and premotor representations, suggesting a strict link between emotion and action.